Comorbid pathology in patients with late-stage ankylosing spondylitis - E. S. Yushina; E. V. Zonova; E. B. Luksha; D. N. Orlov; V. V. Rerikh; V. N. Koksharova (Современная ревматология)
Objective: to investigate the frequency and characteristics of comorbid diseases in patients with late-stage ankylosing spondylitis (AS).Material and methods. The study includes 40 men aged 33–67 with late-stage AS (main group) and 40 patients with a cardiovascular conditions (control group). We analyzed clinical characteristics of AS in patients of the main group. In addition, echocardiography (EcoCG) and ultrasound of brachiocephalic arteries (BCA) were done in patients of both groups to assess patients' cardiovascular condition.Results and discussion. The mean age of the patients was 49.90±9.44 years, and the mean duration of the disease was 24.07±9.72 years. 85% of patients suffered from arterial hypertension (AH), mainly grade 1 and 2 (37.5% each). Body mass index >25 kg/m2 was found in 55.0% (n=22) of patients, predominantly grade 1 and 2 (30.0%, n=12). Hypercholesterolemia was found in 62.5% of patients and an increase in lowdensity lipoprotein cholesterol in 57.5%. The incidence of diabetes mellitus (DM) was 10%. DM type 2 and LADA were found in a ratio of 1:1 (5.0% each). The differences in results of EcoCG and BCA ultrasound in the main and control group were not statistically significant.Conclusion. AH and metabolic disorders occupy the leading place among cardiovascular diseases (CVD) in patients with stable spinal deformity, which can be considered as an additional risk factor for CVD. The data obtained indicate the need to assess cardiovascular risks at an early stage of AS to prevent CVD.